NaOH-embedded three-dimensional porous boron nitride for efficient formaldehyde removal. (5th November 2015) - Li, Jie; Jia, Huichao; Ding, Yushi; Luo, Han; Abbas, Saleem; Liu, Zhenya; Hu, Long; Tang, Chengchun
Abstract: Volatile organic compounds, especially formaldehyde (HCHO), are considered to be great sources of contaminants in indoor air. However, design and preparation of safe, cost-affordable, and reusable materials for HCHO removal at ambient conditions are still remarkably challenging. Here, we have developed a kind of novel NaOH-embedded three-dimensional porous boron nitride (NaOH-3D BN) with high and hierarchical porosities, which exhibit excellent removal performance for HCHO. The as-prepared 3D BN is used as an adsorbent and catalytic support, while the embedded NaOH is applied as a catalyst, giving rise to catalytic transformation from high-toxic HCHO to less-toxic formate and methoxy salts at room temperature. Furthermore, their effective reusability has been confirmed. Given the high removal and reusability performance as well as no use of precious materials, the NaOH-3D BN is envisaged to be valuable practically for indoor air purification.